Apoptotic potential of bioactive fraction isolated from Aliidiomarina taiwanensis KU31894 against skin (A375) cancer cell lines (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
In the present study, the marine bacteria Aliidiomarina taiwanensis KU31894 was used. The bioactive secondary metabolites extracted from marine bacteria A. taiwanensis KU31894 were found to exhibit anticancer activity. The cell-free supernatant of the bacterial culture was extracted with ethyl acetate and showed effective cytotoxicity against skin cancer (A375) cell line, with IC50 concentration of 83.01 ± 1.6 μg/mL by MTT assay. Bioassay-guided fractionation of the ethyl acetate was done by silica gel column chromatography using gradients of the solvent system (chloroform: methanol). Fraction 7 exhibited cytotoxicity, with an IC50 concentration of 59.13 ± 2.53 μg/mL. The bioactive fraction treated cancer cell lines showed morphological changes such as cell shrinkage, rupture of the nuclear membrane, and chromatin condensation was visualized by AO/EB staining. Flow cytometric analysis of treated cancer cells showed a decreased concentration of DNA in the S phase and results in G0/G1 phase arrest. Apoptotic-related gene expression studies of treated cells illustrated the increased expression of pro-apoptotic gene Bax and tumor suppressor gene p53 and decreased expression of anti-apoptotic genes (Bcl-2 and Bcl-xL). These are the primary molecular mechanism following the implementation of apoptosis. The results concluded that A. taiwanensis KU31894 exhibit significant anticancer activity against skin cancer (A375) cells.